Dynamo action and magnetic activity during the pre-main sequence: Influence of rotation and structural changes. Issue Volume 12:Issue S328(2016) (12th September 2017) - Emeriau-Viard, Constance; Brun, Allan Sacha
Abstract: During the PMS, structure and rotation rate of stars evolve significantly. We wish to assess the consequences of these drastic changes on stellar dynamo, internal magnetic field topology and activity level by mean of HPC simulations with the ASH code. To answer this question, we develop 3D MHD simulations that represent specific stages of stellar evolution along the PMS. We choose five different models characterized by the radius of their radiative zone following an evolutionary track, from 1 Myr to 50 Myr, computed by a 1D stellar evolution code. We introduce a seed magnetic field in the youngest model and then we spread it through all simulations. First of all, we study the consequences that the increase of rotation rate and the change of geometry of the convective zone have on the dynamo field that exists in the convective envelop. The magnetic energy increases, the topology of the magnetic field becomes more complex and the axisymmetric magnetic field becomes less predominant as the star ages. The computation of the fully convective MHD model shows that a strong dynamo develops with a ratio of magnetic to kinetic energy reaching equipartition and even super-equipartition states in the faster rotating cases. Magnetic fields resulting from our MHD simulations possess a mixed poloidal-toroidal topology with no obvious dominant component. We also study the relaxation of the vestige dynamo magnetic field within the radiative core and found that it satisfies stability criteria. Hence it does not experience a global reconfiguration and instead slowly relaxes by retaining its mixed poloidal-toroidal topology.